GAMBARAN TINGKAT PENDIDIKAN DAN USIA IBU HAMIL DENGAN PENGETAHUAN TENTANG BAHAYA PRE-EKLAMSIA BERAT - Rumjati Rumjati; Sri Wahyuni (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2012)
Hard pre-eclampcy is pregnancy complication with the rise of hypertency ≥160/110 mmHg anf also protein urine and oedema, in 20 weeks or more pregnancy. In Indonesia pre-eclampcy case in one of the main cause of mother and baby death. It has been found that the mother death around 9,8% - 25,5% and for the baby death was more high, eround 42,2% - 48, 9%. The education level and age was influenced somebody knowledge and comprehension. The hinger of someone education level the higher his comprehension level, so that could help some body in getting and comprehending any information, especially healty problems.The objective of this reseach was to find out the description of pregnant mother education level and age in comprehending the denger of pre-eclapmcy in independent Midwifery Clinic Fauziah Hatta Palembang Tahun 2010.The resech was description research through suevey approachmen. The population of this research was all the pregnant mother who investigating their pregnancy and health in independent Midwifery ClinicFauziah Hatta Palembang Tahun 2010 where 34 respondences as reseach sample which was collected by using accidental sampling. The data were analyzed as univariat analysis. The data analysis that described in percentage form.The result of the research found tha from 34 pregnant mother with in comprehending the danger of pre-eclampcy were 7 respondences (20,59%) and te mother with low comprehending the danger of pre-eclampcy were 19 respendences (55,88%). And for the mother with no comprehension of pre-eclampcy were 8 respondences (23,53%).Pregnant Mother Education Level (High ≥SMA and low <SMA) and age in pregnant (young <20 years , while 20-35 years, and old ≥35 years), knowing level the people because education level what high and mother age 20-35 years easy people to reserue and concept information what is ti think a lready a dult well the mother, the superior problem to healths.